Age, sex incidence with signs and symptoms of peritonitis - ML, Ramachandra (International Journal of Research in Medical Sciences, 2017)
Background:Peritonitis, while no longer the over whelming problem it once was, is still the most common cause of death, ballooned surgical treatment of abdominal disease. In 5 to 7 present of all autopsies, peritonitis is either the primary or a contributory cause of death. Therefore the present study has been undertaken to find out the actual cause of death peritonitis. Methods:This study was conducted after the institutional ethical clearance and informed written consent from all the subjects. Fifty surgically proved perforative peritonitis cases admitted to the surgical wards were included in the study. Radiological examination was done in all the cases to detect pneumoperitoneum. Ulcer edge biopsy was taken from peptic and non-specific ileal perforations. The data are expressed as mean and the percentile was calculated in each parameters. Results:90% of the subjects were males and the patients belong to the age group of 31-40 years. Of the 32 cases of perforated peptic ulcer, 19 gave the previous history of pain abdomen lasting from 6 months to 15 years, one gave the history of fever and in 14 cases there was no history. The pneumoperitoneum is demonstrable on X-ray in 60-80% cases of peptic as well as non-traumatic small bowel perforations. Conclusion:The study showed that the maximum mortality occurred in those patients who were admitted to the hospital after more than 24 hours from the time of appearance of the first symptom. Therefore, it is advised not to delay in attending the hospital rather than delayed surgery.